Paraphrasing challenges faced by Malaysian ESL students - Adi Badiozaman , Ida Fatimawati (Issues in Language Studies, 2014)
This study examined the challenges faced by Malaysian second language (L2) learners when paraphrasing an academic text. Drawing on interviews with two diploma students from two business majors, I explored the types of challenges they faced when attempting paraphrasing tasks. The findings revealed that the students faced multiple challenges that ranged from text comprehension, poor L2 proficiency to referencing problems. In addition, there were significant differences between paraphrasing strategies adopted by a competent student and one with a lower proficiency level. Overall, the findings suggest that there is a need to utilise Content-Based Instruction to make the links between writing skills and learners’ disciplines tangible and that pre-degree preparation needs to include extensive writing practice which would help students become familiar with academic writing demands. Preliminary results also show that there is a need for teachers to be aware that the design of the materials for English language teaching should be tailored to the purpose of university study and academic vocabulary.